Enhancing organizational performance with social media use: the catalysing effect of corporate entrepreneurship - Martín-Rojas, Rodrigo; García-Morales, Víctor J.; Garrido-Moreno, Aurora (My University, 2019)
Social Media use has become pervasive and firms are increasingly relying on it, not only to relate to customers, but also to leverage internal processes like innovation. The strategic use of these tools can facilitate also the entrepreneurial orientation of the firm, as it provides useful knowledge which can make the firm more entrepreneurial, stimulating it to find new opportunities or innovative ideas where other companies do not recognize them. However, despite the relevance of the phenomenon in current hyper-competitive environments, empirical research on the topic remains scarce. To shed some light on the issue, the main purpose of the paper is to examine how Social Media use impacts the different dimensions of corporate entrepreneurship (new business venturing, innovativeness, proactiveness and self-renewal), enhancing also organizational performance. The study is intended to extend knowledge on this topic, by providing understanding of the path firms should take to benefit from Social Media use to become more entrepreneurial and achieve higher organizational performance, developing and nurturing competitive advantages. The paper analyses data obtained from a sample of 201 technological firms located in Spain. The methodology used is Structural equation modelling with LISREL analysis. Findings confirms how the use of Social Media tools positively impacted all the different dimensions of corporate entrepreneurship, translating also in enhanced performance. This paper contributes to the literature by empirically confirming in a structural model how Social Media use helps to create business value, by enhancing proactive behaviours, promoting strategic renewal inside the firm and increasing innovativeness and new business venturing and displaying the internal and sequential relationships among these dimensions.
Keywords: Medios de comunicación social; Redes sociales; Empresas; Congresos y conferencias; SOCIAL MEDIA TOOLS; CORPORATE ENTREPRENEURSHIP